Digital therapeutics for cardiovascular diseases in India- a low-middle income country’s perspective: a systematic review - Prabhughate, Ashwin; Gharat, Chetan (International Journal of Research in Medical Sciences, 2024)
Cardiovascular disease acts as a predominant cause for death in India. Digital technology has shown great potential in delivering cardiac rehabilitation remotely to patients with minimal cost implications. The main aim of this study was to analyze the comprehensiveness and effectiveness of digital cardiac rehabilitation intervention for cardiovascular patients on the Indian Cardiology Continuum. A comprehensive literature search was performed in Pubmed, Springer-link, Elsevier, Embase and Google Scholar. The selected tenure for this review was 10 years (16 January 2014 to 16 January 2024). Authors separately conducted the assessment of the selected studies by using the quality assessment of diagnostic accuracy studies. Microsoft excel 2020 was used for statistical analysis and graphical designs. A total of 3 articles were included in the review. The median sample size of the included studies is 153 (30-304), mean study timeline is 7.67 months (3-17), and median follow-up period is 6 months (3-12). Digital therapeutics showed significant reduction in Systolic Blood Pressure (34.67 mmHg) and Diastolic Blood Pressure (21.97 mmHg) in stage III hypertensive patients. Medication adherence of patients using digital therapeutics was 90%, while 10% patients remained non-adherent/dropped out of the trial. Digital therapeutics builds a lucrative bridge to help cardiovascular patients cross over into improved QoL, in place of traditional face-to-face CR regimes. Further research is required to improve comprehensiveness and clinical effectiveness of the digital cardiac rehab programs on a long-term basis in India.